THERMAL INSULATION MATERIAL MADE FROM OIL PALM EMPTY FRUIT BUNCH FIBRES - Erwinsyah; C. Richter (BIOTROPIA, 2007)
The objectives of this study were to characterize cut oil palm empty fruit bunch (EFB) fibres to focus on the manufacturing of environmentally friendly thermal insulation material from these fibres for building purposes.